PEMANFAATAN QR-QRIS SEBAGAI CASHLESS DI ERA DIGITALISASI PADA UKM BINAAN UI-IBU MALANG - Kurniawan, Faizal; Novariyanto, Rizki Agung; Chandra, Eddy (STIA MALANG, 2026)
The integration of the Indonesian Standard Quick Response Code (QRIS) is a crucial strategic step for Micro, Small, and Medium Enterprises (MSMEs) to modernize their payment infrastructure, thereby catalyzing the acceleration of the digital economy amid widespread digital transformation. This standardized payment system represents a foundational technological breakthrough, establishing a universal framework for QR-based non-cash transactions. Crucially, MSMEs are empowered to consolidate various payment platforms—spanning digital wallets, electronic money applications, and mobile banking services—under one unified QRIS logo. This eliminates the necessity for enterprises to manage multiple proprietary codes. The widespread implementation of QRIS furnishes smaller enterprises with a streamlined, highly effective mechanism to successfully transition towards a cashless operational model, significantly enhancing the fluidity and overall efficiency of financial exchanges. An analysis derived from a targeted investigation conducted in the Tlogmas area of Malang City, Indonesia, indicates that the assimilation of QRIS yields varied outcomes for local MSMEs. The findings underscore the system's inherent capacity to boost operational productivity and open up new market avenues, provided it is complemented by robust technological infrastructure and greater entrepreneurial literacy regarding its full scope of advantages. These observations necessitate proactive policy intervention aimed at heightening MSME proficiency and participation in the utilization of QRIS. It is incumbent upon governing bodies and associated entities to escalate outreach efforts and conduct extensive informational campaigns detailing QRIS benefits. Furthermore, targeted capacity building programs are essential to ensure MSME proprietors possess comprehensive technical mastery, enabling them to optimally leverage this digital payment technology not just for transactional expediency, but as a robust driver for business continuity and long-term sustainable expansion.